Correlation of the Dimensions of Hand & Feet with Stature of an Individual: A Study on Central Indian Adults - Mohite, Prakash M; Keche, Atul S; Mohite, Deepali P; Keche , Harsha A (Journal of Indian Academy of Forensic Medicine, 2015)
Identification of Human remains is a crucial problem and is of utmost importance to Forensic experts. Human beings are considered bilaterally symmetrical. Prediction of stature can be given from long bone measurements with certain degree of accuracy. The present study was done to find out the correlation between the Hand length, breadth & Foot length to the stature of an individual and to arrive at a regression formula. The prospective study was carried out on 230 Students (120 Male & 110 Female) between the age group of 17-25 years studying in Medical & Dental College in Sawangi (Meghe) Wardha. To avoid diurnal variations all the measurements were taken at a particular period of time. The students born & brought up in Central India only were included in the study. The dimension of the hand which was dominant was taken. There is a definite correlation between Stature & Dimensions of Hand and Foot as is derived from a regression formula which may help the forensic experts in estimating Stature in mutilated or fragmented bodies.